Diseño e implementación de una red de aplicaciones bancarias e internet para la cooperativa de ahorro y crédito pequeña empresa de pastaza y sus agencias. - Vallejo Barragán, Byron Ronald (2013)
In order to improve the quality and service of the Cooperative Savings and Credit Small Business of Pastaza this project addresses the design and implementation of a network link and internet banking applications through the limited company Equysum. The problem is the link between the parent and the agency Puyo Ambato, there is packet loss and delay very high with the link provided in another company and Tena and Macas agencies lacked the data link service.